ANALISIS PROFITABILITAS PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Selvi Kartika Pratiwi (2021)
The purpose of this research is to know the impact of capital structure, dividend policy and sales growth on profitability. The study takes population of 65 property and real estate companies listed on the Indonesian stock exchange. This study used the technique of purposive sampling to complete the sampling selection and produced samples of 13 property and real estate companies. Hypothesis testing and analysis of the data are using data regression analysis, and the data regression analysis is performed with the assist of E-views 9.0 with a 5% as significance level. The result of this study is that capital structure (DER) has no significant impact on profitability (ROA), dividend policy (DPR) has no significant impact on profitability, and sales growth also has a significant impact on profitability.